2012
DOI: 10.1007/s00125-012-2464-x
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic expression of glucagon receptor in skeletal muscles improves glucose homeostasis in a mouse model of diabetes

Abstract: Aims/hypothesis Excessive secretion of glucagon partially contributes to the development of diabetic hyperglycaemia. However, complete blocking of glucagon action will lead to adverse effects, since glucagon exerts certain beneficial effects via its receptor in many organs. We aimed to study the effects of a 'decoy receptor' for circulating glucagon on modulating beta cell function and glucose homeostasis in mice by over-producing the glucagon receptor (GCGR) in skeletal muscles. Methods We generated transgeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Furthermore, pancreas perfusion studies using specific GCGR antagonists suggested that the intra-islet glucagon-induced trophic effects on the β-cells are mainly through GCGR rather than GLP-1 receptors on islet β-cells (Kawai et al, 1995), although the gut-derived insulinotropic hormone is recently found to be also produced by the α-cells and exerts local actions (Marchetti et al, 2012). The intra-islet trophic effects of glucagon have been further studied using transgenic mice expressing GCGR under control of the muscle specific creatine kinase (Mck) promoter (Maharaj et al, 2012). The Mck/Gcgr mice, which displayed mild hyperglucagonemia (but unchanged circulating GLP-1 levels), are euglycemic under basal conditions but are resistant to streptozotocin-induced β-cell injury partially due to enhanced intra-islet action of both glucagon and insulin on β-cell competence (Maharaj et al, 2012).…”
Section: Mechanisms Of Glucagon Actionmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, pancreas perfusion studies using specific GCGR antagonists suggested that the intra-islet glucagon-induced trophic effects on the β-cells are mainly through GCGR rather than GLP-1 receptors on islet β-cells (Kawai et al, 1995), although the gut-derived insulinotropic hormone is recently found to be also produced by the α-cells and exerts local actions (Marchetti et al, 2012). The intra-islet trophic effects of glucagon have been further studied using transgenic mice expressing GCGR under control of the muscle specific creatine kinase (Mck) promoter (Maharaj et al, 2012). The Mck/Gcgr mice, which displayed mild hyperglucagonemia (but unchanged circulating GLP-1 levels), are euglycemic under basal conditions but are resistant to streptozotocin-induced β-cell injury partially due to enhanced intra-islet action of both glucagon and insulin on β-cell competence (Maharaj et al, 2012).…”
Section: Mechanisms Of Glucagon Actionmentioning
confidence: 99%
“…The intra-islet trophic effects of glucagon have been further studied using transgenic mice expressing GCGR under control of the muscle specific creatine kinase (Mck) promoter (Maharaj et al, 2012). The Mck/Gcgr mice, which displayed mild hyperglucagonemia (but unchanged circulating GLP-1 levels), are euglycemic under basal conditions but are resistant to streptozotocin-induced β-cell injury partially due to enhanced intra-islet action of both glucagon and insulin on β-cell competence (Maharaj et al, 2012). …”
Section: Mechanisms Of Glucagon Actionmentioning
confidence: 99%
See 3 more Smart Citations